Answer:
o
Step-by-step explanation:
if x = 0 ,y =10
4×0+10
=10
if x = 1, y = 6
=4×1 + 6
=4 +6
=10
if x = 2, y = 2
=4×2 +2
=8 + 2
=10
u can substitute any value for x and y ...i have only used positive values here
Answer:
Answer is 81y^4z^4
Step-by-step explanation:
The expression is (-3yz) (-3yz) (-3yz) (-3yz).
Since all the four terms have power 1:
(-3yz)^1 (-3yz)^1 (-3yz)^1 (-3yz)^1
We know that we can add the powers if the terms have same base
So,
=(-3yz)^1+1+1+1
=(-3yz)^4
=(-3)^4(y)^4(z)^4.
If the power is an even number than the negative sign changes into positive sign.
=3^4y^4z^4
=81y^4z^4
Thus the answer is 81y^4z^4....
Answer:
a = 6
Step-by-step explanation:
Hello!
Solve:
- 4(3a - 4) = 56
- 3a - 4 = 14 (factoring out 4)
- 3a = 18 (adding 4 to both sides)
- a = 6 (dividing by 3)
Another way:
- 4(3a - 4) = 56
- 12a - 16 = 56 (distributive property)
- 12a = 72 (moving like terms)
- a = 6 (dividing by 12)
Distributive Property of Multiplication:
The process of distributing the outside factor to the terms in the parenthesis.
Example:
![4(3a - 4)\\\\4(3a) - 4(4)\\\\12a - 16](https://tex.z-dn.net/?f=4%283a%20-%204%29%5C%5C%5C%5C4%283a%29%20-%204%284%29%5C%5C%5C%5C12a%20-%2016)
I have no clue I don’t understand this